American Medical Society for Sports Medicine (AMSSM) Position Statement: Interventional Musculoskeletal Ultrasound in Sports Medicine. Issue 2 (20th February 2015) - Finnoff, Jonathan T.; Hall, Mederic M.; Adams, Erik; Berkoff, David; Concoff, Andrew L.; Dexter, William; Smith, Jay
Abstract: The use of diagnostic and interventional ultrasound has significantly increased over the past decade. A majority of the increased utilization is by nonradiologists. In sports medicine, ultrasound is often used to guide interventions such as aspirations, diagnostic or therapeutic injections, tenotomies, releases, and hydrodissections. This American Medical Society for Sports Medicine (AMSSM) position statement critically reviews the literature and evaluates the accuracy, efficacy, and cost‐effectiveness of ultrasound‐guided injections in major, intermediate, and small joints, and soft tissues, all of which are commonly performed in sports medicine. New ultrasound‐guided procedures and future trends are also briefly discussed. Based upon the evidence, the official AMSSM position relevant to each subject is made.